Predictor Factors of Return to Work in Workers with Kidney Transplantation in Iran: A Retrospective Cohort Study (Iranian Journal of Kidney Diseases, 2023)
Introduction. Return to work after a kidney transplantation in a previously functioning person is determined by a number of medical and non-medical factors. In this regard, this study was to investigate the factors that influence return to work in kidney transplant recipients. Methods. This retrospective cohort study was conducted in patients with kidney transplant in the main nephrology center in Tehran (December to April 2022). The primary outcome was the cumulative rate of return to work at 3, 6, and 12 months after transplantation. The secondary outcome was to compare the occupational, individual, and disease-related factors between patients who had returned to work and those who had not. Results. Among 214 kidney transplant recipients, the overall cumulative rate of return to work after kidney transplantation at 3, 6 months, and 12 months were 44.4%, 63.1% and 69.6%; respectively. According to the univariate analysis, male sex, age less than 40 years, nonphysical jobs, job satisfaction, employer support, partner support, and absence of diabetes mellitus significantly affected the time of return to work (P < .05). According to the multivariate analysis, absence of diabetes mellitus, nonphysical jobs and job satisfaction had greater impact on the time of return to work (P < .05). Conclusion. The results showed that older age, female gender, having a physical job, the presence of diabetes mellitus, lack of job satisfaction, and employer and partner support are associated with not returning to work in these patients and adjusting factors linked to the work environment and support of colleagues and supervisors might play an important role in improving the general condition of these patients.  DOI: 10.52547/ijkd.7210